Quarter Life Crisis di Kalangan Mahasiswa - Putri Resha; Grendi Hendrastomo (Sociology Study Program, Faculty of Social Science and Law, Universitas Negeri Jakarta, 2024)
Quarter life crisis is a term used to describe a period of uncertainty generally experienced by adults in their 20s. This research aims to explore the phenomenon, identify factors, and describe students attitudes in dealing with quarter life crisis. The research informants consisted of seven students in the Special Region of Yogyakarta from the D3, D4, S1 and S2 levels. This research is descriptive qualitative research that uses purposive sampling as a subject determination. The data analysis techniques used is interactive model including Data Condensation, Data Presentation, and Consclusion Drawing. Data collection techniques use observation and interviews. Based on the research results, it was found that the quarter life crisis experienced by informants with informants with D3, D4, and S1 education levels was more complex crisis than informants with masters education levels. The crisis experienced by informant was caused by internal and external factors as well as many demands in the form of career paths, finances, education and interpersonal relationships. Quarter life crisis has an impact on mood and reduced self-confidence which then continues to compare. Each informant has there own way and strategy to survive in quarter life crisis.